A short review on NIR-II organic small molecule dyes. (December 2020) - Li, Lu; Dong, Xugang; Li, Jingru; Wei, Juan
Abstract: Small organic molecules with absorption and/or fluorescence emission in the second near-infrared (NIR-II, 1000–1700 nm) bio-window attracted much attention in the past decades. Benefiting from their intrinsic properties such as low toxicity, fast excretion rate, good biocompatibility, versatile structures, deep tissue penetration, high imaging resolution, and low auto-fluorescence, NIR-II small organic emitters became outstanding candidates for clinical application among the numerous inorganic and organic fluorophores. However, the research is still in the initial lab stage and lots of efforts need to put into clinical practice. In this review, we presented the previous and current status of NIR-II small organic emitters based on different skeletons, as well as their application in bioimaging and theranostics. Furthermore, current challenges and perspectives of these molecules are discussed. Highlights: Previous and current status of different NIR-II small organic emitters and their bio-applications were presented. NIR-II organic small molecule dyes were legibly classfied according to different skeleton. Present challenges and perspectives of NIR-II outstanding clinical candidates were discussed.